The effect of telerehabilitation on early outcomes in patients undergoing primary total knee replacement: A prospective randomized study - Şahin, Adem; Agar, Anıl; Ertürk, Cemil (Journal of Surgery and Medicine, 2022)
Background/Aim: The continuity of rehabilitation is a problem after arthroplasty operations. There is a need for accessible rehabilitation programs for patients. The purpose of this study is to determine the difference in knee functions and patients’ quality of life between patients doing home telerehabilitation and home rehabilitation after total knee arthroplasty (TKA). Methods: This prospective study was conducted on 90 patients, between June 2019 and January 2021. Patients are divided into three groups. Patients in group 1 are told to continue with the daily routine exercises which began in hospital. Group 2 patients got an information message to their mobile phones every day for the first month, reminding them of their postoperative exercises, whereas patients in group 3 are called by mobile phone for the same reminding. All patients participating in the study were evaluated by completing the Universities of Western Ontario and McMaster Osteoarthritis Index (WOMAC) scores, the Knee Society Clinical Evaluation System (KSS), the Barthel Index (BI) and the Quality of Life Scale Short Form 36 (SF-36) preoperatively and in the first and third months postoperatively, and the differences between the groups based on these scores were evaluated. Results: There was a statistically significant difference in WOMAC between the groups regarding first-month and third-month postoperatively (P=0.004 and P<0.001, respectively), as well as in KSS values between the same groups (P=0.048 and P=0.036, respectively). There was no statistically significant difference between the groups regarding postoperative first-month BI (P=0.826) and SF-36 values (P=0.264). There was a statistically significant difference between the groups regarding postoperative third-month BI and SF-36 values (P=0.035 and P<0.001, respectively). Conclusion: The telerehabilitation therapy appears to be more effective and successful than the control group, as shown by improvements in overall physical functions.